From the mixed-up files of Mrs. Basil E. Frankweiler / E L Konigsburg - Konigsburg, E. L.
Having run away with her younger brother to live in the Metropolitan Museum of Art, twelve-year-old Claudia strives to keep things in order in their new home and to become a changed person and a heroine to herself.